Immunoglobulins in tracheo-bronchial secretion with special reference to IgE - Deuschl, H. (1974)
Quantitative measurements of immunoglobulins E, A and G were made in tracheobronchial secretion and serum of thirty-four patients in association with bronchoscopy. Measurable quantities of all three immunoglobulins were found in both secretion and serum in all patients, except in one person, in whom IgA was found neither in the secretion nor the serum, and in another person in whom no measurable IgG was found in the secretion. Calculations indicated that all immunoglobulins were produced locally in the tracheo-bronchial mucosa. This applied especially to IgA and IgE, of which 84 and 73% respectively, were calculated to have been produced locally. Quantitative differences between the three immunoglobulins were also apparent between different groups of patients. The number of patients studied is too small, however, for definite conclusions to be drawn in this respect.